Paul Martsching letter to Thomas Kent regarding Greater Scaup documentation, November 27, 1985 - Martsching, Paulet al (1985)
Paul Martsching mentions sighting a Greater Scaup at Hickory Grove, White-winged Scoter at Saylorville and Lapland Longspur all over Story County. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed